Üniversite öğrencilerinin gestalt temas biçimleri ile yaşam doyumları arasındaki ilişkinin incelenmesi - Gürsoy, Ülkü (My University, 2009)
ÜNİVERSİTE ÖĞRENCİLERİNİN YAŞAM DOYUMU İLE GESTALT TEMAS BİÇİMLERİ ARASINDAKİ İLİŞKİ Bu araştırmanın temel amacı, üniversite öğrencilerinin gestalt temas biçimleri ile yaşam doyumları arasındaki ilişki olup olmadığının incelenmesidir. Gestalt temas biçimleri ve yaşam doyumunun cinsiyet, öğrenim görülen fakülte, sınıf düzeyi, öğrenim gördükleri bölümden memnuniyet durumları, sosyo-ekonomik düzey, anne eğitim durumu, baba eğitim durumu, anne tutumu ve baba tutumu değişkenlerine göre farklılaşıp farklılaşmadığının belirlenmesi de araştırmanın alt amaçlarını oluşturmaktadır. İlişkisel tarama modeline uygun olarak düzenlenmiş araştırmanın evreni Marmara üniversitesi öğrencileri, örneklemi ise 2008-2009 öğretim döneminde Marmara Üniversitesi’nin Atatürk Eğitim, Fen-Edebiyat, Mühendislik, Hukuk, Eczacılık Fakülteleri ve Hemşirelik Yüksek Okulunda öğrenim görmekte olan 261’i kız 201’i erkek olmak üzere toplam 462 lisans öğrencisidir. Araştırmada veri toplama aracı olarak, araştırmacı tarafından hazırlanan “Kişisel Bilgi Formu” aynı zamanda “Gestalt Temas Biçimleri Ölçeği” ve “Yaşam Doyumu Ölçeği” kullanılmıştır. Veri analizleri sonucunda, üniversite öğrencilerinin, yaşam doyumları ile kendine döndürme ve saptırma temas biçimleri arasında orta şiddette (p<,01), pozitif yönde, temas temas biçimi arasında orta şiddette (p<,01) negatif yönlü anlamlı ilişki tespit edilmiştir. Buna karşın üniversite öğrencilerinin yaşam doyumları ile iç içe geçme ve duyarsızlaşma temas biçimleri arasında anlamlı bir ilişki tespit edilmemiştir. Yaşam doyumu toplam puanları incelendiğinde cinsiyet, öğrenim gördükleri fakülte, öğrenim gördükleri bölümden memnuniyet durumu, sosyo- ekonomik düzey, algılanan anne tutumu ve algılanan baba tutumu değişkenleri arasında istatistiksel olarak anlamlı fark bulunmuştur. Öğrencilerin yaşam doyumu puanları arasında sınıf düzeyi, anne eğitim durumu ve baba eğitimdurumu değişkenlerine göre anlamlı bir fark bulunmamıştır. Üniversite öğrencilerinin temas ve kendine döndürme temas biçimi puanları cinsiyet değişkenine göre anlamlı fark göstermezken, saptırma, iç içe geçme, duyarsızlaşma temas biçimi puanları ile cinsiyet değişkeni arasında anlamlı fark tespit edilmiştir. Üniversite öğrencilerinin duyarsızlaşma temas biçimi puanları ile öğrenim gördükleri fakülte değişkenine göre anlamlı fark varken diğer temas biçimleri arasında anlamlı bir farklılık bulunmamıştır. Yine üniversite öğrencilerinin kendine döndürme temas biçimi puanları ile algıladıkları baba tutumu değişkenine göre anlamlı düzeyde fark bulunmuştur. Buna karşın üniversite öğrencilerinin saptırma, temas, iç içe geçme, duyarsızlaşma temas biçimi puanları ile algılanan baba tutumu arasında anlamlı bir fark bulunmamıştır. Üniversite öğrencilerinin gestalt temas biçimleri (kendine döndürme, saptırma, temas, iç içe geçme, durasızlaşma) okuduğu bölümden memnuniyet durumu, sosyo-ekonomik düzey, anne eğitim düzeyi, baba eğitim düzeyi, algılanan anne tutumu değişkenlerine göre anlamlı bir fark bulunmamıştır. Araştırma bulguları literatür ışığında tartışılmış ve eğitimcilere, araştırmacılara çeşitli önerilerde bulunulmuştur. Gestalt temas biçimi, yaşam doyumu, üniversite öğrencileri

RELATIONSHIP BETWEEN UNIVERSITY STUDENTS’ LIFE SATISFACTION WITH GESTALT CONTACT STYLES The main goal of this study is to examine whether a relationship between life satisfaction of university students with the gestalt contact styles exist or not. Determination of whether gestalt contact styles and life satisfaction differs according to variables like gender, type of faculty pursued, class level, satisfaction status with regards to faculty pursued, socio-economic level, educational status of father educational status of mother, attitude of mother and attitude of father or not constitutes the subgoal of the study. Population of the study conducted in accordance with relational scanning model consisted of Marmara University students while the samples consisted of a total of 462 undergraduate students of which 261 were female and 201 were male who were receiving education in Atatürk Education, Science Literature, Engineering, Law, Pharmacy Faculties and School of Nursing of Marmara University in 2008-2009 education period. The Personal Information Form, “Scale of Gestalt Contact Forms and Life Satisfaction Scale , prepared by the researcher, were used in the study as data collection tools. As a result of the data analysis a relationship of medium force (p<, 01) in the positive direction between life satisfaction and retroflection and deflection and a relationship of medium force (p<,01) in the negative direction between life satisfaction and contact contact style was determined. Despite this, no meaningful relation between the life satisfaction of the university students and confluence and desensitization contact styles was determined. When the life satisfaction total scores were examined statistically significant meaningful difference was found between variables like gender, type of faculty pursued, satisfaction status with regards to faculty pursued, socio-economic level, attitudes regarding perception of mother and attitudes regarding perception of father. No meaningful difference was found between variables like class level, educational status of father and educational status of mother in the life satisfaction scores of the students. Contact and retroflection contact style scores did not reflect difference according to the gender variable whereas meaningful differences were determined between the deflection, confluence, desensitization contact styles, and gender variable. A meaningful difference was determined between retroflection and deflection contact styles of university students according to class level variable whereas no meaningful difference between other contact styles was determined. Despite this a meaningful difference was determined between desensitization contact style scores according to the pursued faculty variable whereas no meaningful difference between other contact styles was determined. A meaningful difference was determined between deflection contact style scores of university students according to the satisfaction status with regards to faculty pursued variable whereas no meaningful difference between other contact styles was determined. A significant meaningful difference level was determined between retroflection contact styles scores of university students according to the attitudes regarding perception of father determined. Despite this no meaningful difference was determined between deflection, contact, desensitization, confluence contact style scores of university students according to the attitudes regarding perception of father determined. Gestalt contact styles of university students (retroflection, deflection, contact, confluence, desensitization) did not reflect any significant meaningful difference according to variables of satisfaction status with regards to satisfaction of the faculty pursued, socio-economic level, educational status of father, educational status of mother, attitudes regarding perception of mother. The research findings were discussed in the light of current litterateur and several proposals have been submitted to educationalists and researchers. Key words: Gestalt contact style, life satisfaction, university students
Keywords: Öğrenim ve Öğretim; Rehberlik ve Psikolojik Danışmanlık; Üniversiteler ve Yüksekokullar; Yaşam Kalitesi